META ANALISIS EFEKTIVITAS PEMBELAJARAN ETNOMATEMATIKA TERHADAP KEMAMPUAN BERPIKIR MATEMATIS SISWA INDONESIA - Susanto, Nabilla Calista Putri; Purnamasari, Hetty; Wahjuningtyas, Sri (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2023)
This study aims to synthesize the effect of ethnomathematics learning on students' mathematical thinking abilities. Data were obtained from primary studies in the form of journals in the 2018-2023 range. Six studies that met the inclusion criteria were analyzed using JASP 0.17.3 software. The results showed that ethnomathematics learning had a very strong influence on students' mathematical thinking abilities (gRE= 1,714; 95% CI [0,983; 2,446]; p 0,001). when compared to traditional learning. As for the results of the analysis of the moderator variable, it shows that the engagement variable (Qb = 7,841; p = 0,005) and education level (Qb = 27,505; p = 0,000) have a significant influence on the effectiveness of ethnomathematics learning on mathematical thinking skills. The results of this study provide important information regarding future meta-analytic research and the application of ethnomathematics in mathematics learning.